Integration management system design - Suprayitno, Gendut; Stendel, Alex Permana (Management and Entrepreneurship: Trends of Development, 2020)
Industrial Sector of Oil and Gas is a strategic point for Indonesia Economical Condition. The purpose of the paper is to design integration model system of Sistem SNI ISO 27001:2013, SNI ISO 37001:2016, SNI ISO 9001:2015, SNI ISO 20400:2017, and ISO 50001:2018 within PAS 99:2012 on Special Task Force for oil and Gas business activities and to identify its dominant factor. This paper presents quantitative-qualitative research with descriptive approach and the analysis of SEM LISREL 8.8. It was started with making a background of study and formulating research problem along with the purpose of analysis and then spreading questionnaire to respondents. The clause of management system is identified and the characteristic features of each management system are descriptively explained in the paper. The result of this analysis determined the structure of SNI ISO 27001:2013 and SNI ISO 37001:2016 as the main standard because Special Task Force of Oil and Gas has been applied that standard. Based on the result, it can be concluded that the significant level of questionnaire results is PAS 99: 2012 from the Integration Management system is obtaining the highest SL value in clause 7 at 0.99. According to PAS 99: 2012, clause 7 is a factor that supports the Integration Management System.JEL Classification: P41, P00